2009
DOI: 10.1309/ajcp8ve7awbzcvqt
|View full text |Cite
|
Sign up to set email alerts
|

The Becton Dickinson FocalPoint GS Imaging System

Abstract: Location-guided screening in cervical cytology offers a potentially significant advance over routine manual screening. A prospective, 2-armed, masked clinical trial of the BD FocalPoint GS Imaging System using SurePath slides (BD Diagnostics-TriPath, Burlington, NC) compared routine manual screening and quality control rescreening with computer-assisted, field-of-view screening and device-directed quality control rescreening. The results obtained in the 2 arms were compared with adjudicated reference diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…The replacement of manual screening by automated analysis followed by manual screening of merely designated cases has been a matter of debate in many countries worldwide, with conflicting results in the literature [6,7,8]. A recent clinical study in Canada looking at more than 10,000 slides read by the BD FocalPoint showed that the detection of ASC-US and LSIL by automated analysis is significantly lower than that by manual revision of slides, suggesting an improvement in the detection of abnormal cells by the image-guided computer system before it was globally incorporated into clinical practice [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The replacement of manual screening by automated analysis followed by manual screening of merely designated cases has been a matter of debate in many countries worldwide, with conflicting results in the literature [6,7,8]. A recent clinical study in Canada looking at more than 10,000 slides read by the BD FocalPoint showed that the detection of ASC-US and LSIL by automated analysis is significantly lower than that by manual revision of slides, suggesting an improvement in the detection of abnormal cells by the image-guided computer system before it was globally incorporated into clinical practice [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although many papers in the literature discuss the usefulness of automated analysis applied to liquid-based preparations [6,7,8], little is discussed for conventional smears [1,2,9,10], which remain the cheapest and most convenient method for early detection of cervical cancer in low-income countries, where this type of cancer is a major health problem [11]. In the current study, we tested the ability of automated screening using the BD FocalPoint Imaging Analyzer (Becton Dickinson, Franklin Lakes, N.J., USA) in processing conventional gynecological cytology smears as well as its efficacy in assessing sample adequacy and stratifying cases for risk of malignancy when compared to the manual revision of slides.…”
Section: Introductionmentioning
confidence: 99%
“…A review of current devices was reported in 2006 [40], and serves as a starting point for interested readers; however, the field is in a constant and rapid state of change, and hence the newest information on current scanning devices is generally only available from the manufacturers themselves. Many studies of whole-slide imaging technology are available for histopathologic applications, including frozen section and permanent slide applications [2,41,42,43,44,45,46,47,48,49,50]. Only a few reports detail the use of whole-slide images in cytology diagnostic applications [3,51,52].…”
Section: Telediagnosis/teleconsultationmentioning
confidence: 99%
“…In the future, the addition of artificial intelligence and data mining will likely be the next level of digital pathology technology. Already in gynecologic cytology, devices are capable of identifying and ranking potentially abnormal cells, with presentation of these areas digitally to observers for assessments [41]. Transfer of this capability to whole-slide digital images would allow for flexibility in the process because analysis of the slides would not be tied to the physical presence of the slides.…”
Section: Prospects For the Future Of Digital Cytologymentioning
confidence: 99%
“…In addition, focusing of the manual screening process on the remaining high risk cases also showed gains in accuracy with higher sensitivity of detection noted. Later devices extended this principle of ‘focused’ screening to so-called ‘field of view (FOV)’ assessments, where the devices identified the highest risk areas on each slide, with automated microscopes taking cytotechnologists directly to these FOVs [12,13,14]. If no cytologic abnormality is identified in these highest-risk FOVs, the case can be safely labeled as negative (FOV-only review).…”
Section: Introductionmentioning
confidence: 99%